2000
DOI: 10.1093/ageing/29.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Short report. Do patient age and medical condition influence medical advice to stop smoking?

Abstract: Objective: to determine whether the age and medical condition of a patient influences hospital-based doctors' decision making when advising patients to stop smoking cigarettes. Methods: we presented 142 doctors from four grades (consultant, registrar, senior house officer and house officer) and four specialities (medicine, surgery, psychiatry and anaesthetics), based in a Dublin teaching hospital, with 20 clinical vignettes. Each vignette described a patient from one of five age groups with one of four levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 11 publications
2
31
0
1
Order By: Relevance
“…In other words, as suggested by the literature (e.g., Buckland & Connolly, 2005; Gall, Dewey, & Thrift, 2009; Lawrence, Kerr, Watson, & Ellis, 2010; Maguire, et al, 2000), medical and allied health care providers may not be capitalizing on “teachable moments” to the full extent that they could.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, as suggested by the literature (e.g., Buckland & Connolly, 2005; Gall, Dewey, & Thrift, 2009; Lawrence, Kerr, Watson, & Ellis, 2010; Maguire, et al, 2000), medical and allied health care providers may not be capitalizing on “teachable moments” to the full extent that they could.…”
Section: Discussionmentioning
confidence: 99%
“…Maguire, et al (2000) found that, irrespective of an individual’s physical or mental health, hospital-based physicians were significantly less likely to advise patients over the age of 65 years old to quit smoking. This is problematic considering that about three-quarters of all strokes occur in people over the age of 65 (Centers for Disease Control, 2011).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…So, for older people the likelihood of having a serious smokingrelated illness that provides the trigger for strong encouragement to quit is far higher than for the young, and offers healthcare workers, including doctors, a chance to help their older patients to stop smoking that is known to be effective. 46 On the other hand, evidence from North American studies suggests that older smokers are as likely as younger smokers to respond to a targeted smoking cessation campaign, including brief intervention in a primary care setting. Unfortunately, there is evidence that elderly smokers in the UK and USA are far less likely to receive smoking cessation advice from their primary care doctors compared with younger patients, despite the fact that they consult more frequently.…”
Section: Barriers To Giving Up Smokingmentioning
confidence: 99%
“…Further, older patients are less likely to receive cessation counselling or advice (Maguire et al, 2000;Steinberg, Akincigil, Delnevo, Crystal, & Carson, 2006), although they generally welcome such advice (OssipKlein et al, 2000). Even following acute myocardial infarction, only 40% of older (65 years or above) smokers receive counselling on cessation of smoking (Brown et al, 2004), despite its well-established benefits (Wilson, Gibson, Willan, & Cook, 2000).…”
mentioning
confidence: 99%